Case Report: Angiotensin converting enzyme inhibitors vs. angiotensin receptor blockers in the management of chronic hypertension: a case of lisinopril-induced rhinorrhea - Amudzi, Alice A.; Samale, Giro Richard; Vela-Parada, Xavier (Frontiers in Allergy, 2024)
A 47-year-old woman presents to our clinic with a chief complaint of rhinorrhea; she had chronic hypertension managed with four antihypertensive drugs, including an ACE inhibitor. While dry cough is a well-known side effect associated with ACE inhibitors, this case highlights a common chief complaint yet less recognized side effect of ACE inhibitors and further emphasizes the idea that overall, angiotensin receptor blockers may be a better drug of choice in hypertension due to their favorable side effect profile.